An Exploration of Scientific Literacy on Physics Subjects within Phenomenon-based Experiential Learning - Prima Warta Santhalia; Lia Yuliati (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
Abstract Scientific literacy is the ability to involve yourself in problems related to science. This research explores students' scientific literacy skills in experiential learning based on phenomena on the concept of expansion. This research was conducted with a mix-method approach with an embedded experimental model design. The data were collected through scientific literacy tests (r = 0.53), and open-ended questions interviews with the students, then analyzed using the Mann-Whitney U-Test quantitatively, and using the Bybee (1997) assessment rubric qualitatively. Based on the results, it was found that the majority of students experienced an increase in their scientific literacy from the SI (Scientific Illiteracy) category (96.88%) into CSL (Conceptual Scientific Literacy) (46.88%). We concluded that phenomenon-based experiential learning was effective in improving students' scientific literacy. So, we need more effort to improve and increase students' scientific literacy skills by integrating scientific literacy competencies while implementing science learning in schools.